Vertigo Perception and Quality of Life in Patients after Surgical Treatment of Vestibular Schwannoma with Pretreatment Prehabituation by Chemical Vestibular Ablation. (8th December 2016) - Čada, Zdeněk; Balatková, Zuzana; Chovanec, Martin; Čakrt, Ondřej; Hrubá, Silvie; Jeřábek, Jaroslav; Zvěřina, Eduard; Profant, Oliver; Fík, Zdeněk; Komarc, Martin; Betka, Jan; Kluh, Jan; et al.
Abstract : Surgical removal of vestibular schwannoma causes acute vestibular symptoms, including postoperative vertigo and oscillopsia due to nystagmus. In general, the dominant symptom postoperatively is vertigo. Preoperative chemical vestibular ablation can reduce vestibular symptoms postoperatively. We used 1.0 mL of 40 mg/mL nonbuffered gentamicin in three intratympanic installations over 2 days, 2 months preoperatively in 10 patients. Reduction of vestibular function was measured by the head impulse test and the caloric test. Reduction of vestibular function was found in all gentamicin patient groups. After gentamicin vestibular ablation, patients underwent home vestibular exercising for two months. The control group consisted of 10 patients who underwent only home vestibular training two months preoperatively. Postoperative rates of recovery and vertigo in both groups were evaluated with the Glasgow Benefit Inventory (GBI), the Glasgow Health Status Inventory (GHSI), and the Dizziness Handicap Inventory questionnaires, as well as survey of visual symptoms by specific questionnaire developed by us. There were no statistically significant differences between both groups with regard to the results of questionnaires. Patients who received preoperative gentamicin were more resilient to optokinetic and optic flow stimulation (p < 0.05 ). This trial is registered with clinical study registration number NCT02963896 .